Accounting for governmental and nonprofit entities - Wilson, Earl Ra (McGraw-Hill Irwin, 2010)
This textbook provides comprehensive coverage of accounting and financial reporting for all levels of government and not-for-profit organizations, as well as governmental auditing and performance measurement. This fifteenth edition offers two Web-accessible computerized cumulative problems; has been revised to reflect contemporary guidance from the GASB, FASB, FASAB, GAO, OMB, AICPA, and IRS; features new questions, cases, exercises, and problems; and includes expanded coverage of post-employment benefits, major fund reporting, investments and derivatives, IRS Form 990, and budgeting and performance management.